The impact of modern allergens on allergic diseases: A prospective - YRKM Sai (Global Journal of Allergy - Peertechz Publications, 2020)
Allergy is a common condition that affects millions of people worldwide. It is caused by the immune system's abnormal response to harmless substances in the environment, known as allergens.